Enantioselective oxidative cross-dehydrogenative coupling of tertiary amines to aldehydes - Zhang, Junmin (2012)
An enantioselective and direct oxidative coupling of aldehydes to tertiary amines to give β-amino alcohols is described. Catalyzed by copper(II), the reaction proceeds to give a racemic mixture of products; however, by using a combination of copper(II) and a chiral amine catalyst, the reaction gives the desired products with high enantioselectivity.